a) – x = 2x - 3
b) x + 7 = 10 + 6x
c) 3x + 4 = - 2x – 6
d) - 0,3 x – 0,2 = 0,2x + 2
e) – ( 2x + 2) = x
f) 2x – 7 – 2( 3x + 5) = 3
na ast potrzebyje pls


Odpowiedź :

Odpowiedź:

a)

[tex]-x=2x-3\\ -x-2x=-3\\ -3x=-3/:(-3)\\ x=1[/tex]

b)

[tex]x+7=10+6x\\ x-6x=10-7\\ -5x=3/(-5)\\ x=-\frac{3}{5}[/tex]

c)

[tex]3x+4=-2x-6\\ 3x+2x=-6-4\\ 5x=-10/:5\\ x=-2[/tex]

d)

[tex]-0,3x-0,2=0,2x+2\\ -0,3x-0,2x=2+0,2\\ -0,5x=2,2/:(-0,5)\\ x=-4,4[/tex]

e)

[tex]-(2x+2)=x\\ -2x-2=x\\ -2x-x=2\\ -3x=2/:(-3)\\ x=-\frac{2}{3}[/tex]

f)

[tex]2x-7-2(3x+5)=3\\ 2x-7-6x-10=3\\ -4x=3+17\\ -4x=20/:(-4)\\ x=-5[/tex]

Odpowiedź:

a. -x=2x-3. 3x=3/:3. x=1 b.7-10=6x-x. 5x=-3/:5. -1,6=x c.3x+2x=6-4 5x=2/:5. x=0,4. d.-0,3x-0 ,2x=2-0.2. 0,5=1,8/:0,5. x=3,6. e.-2x+2=x. 2=2x+x 3x=2/:3 x=0,6

Szczegółowe wyjaśnienie:

nie wiem czy jest dobrze